The Potential of Isoprenoids in Adjuvant Cancer Therapy to Reduce Adverse Effects of Statins - Mo, Huanbiao; Jeter, Rayna; Bachmann, Andrea; Yount, Sophie T.; Shen, Chwan-Li; Yeganehjoo, Hoda (Frontiers in Pharmacology, 2019)
The mevalonate pathway provides sterols for membrane structure and nonsterol intermediates for post-translational modification and membrane anchorage of growth-related proteins, including the Ras, Rac, and Rho GTPase family. These mevalonate-derived products are also essential for the Hedgehog pathway, steroid hormone signaling, and the nuclear localization of yes-associated protein and transcriptional co-activator with PDZ-binding motif, all playing important roles in tumorigenesis and cancer stem cell function. The mevalonate pathway is upregulated by the phosphatidylinositol-4,5-bisphosphate 3-kinase-AKT-mammalian target of rapamycin complex 1 pathway, p53 with gain-of-function mutation, and oncoprotein MYC and downregulated by adenosine monophosphate-activated protein kinase and tumor suppressor protein RB. The rate-limiting enzyme, 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR), is under a multivalent regulation consisting of sterol-mediated transcriptional downregulation controlled by sterol regulatory element binding protein 2 and UbiA prenyltransferase domain-containing protein-1-mediated ubiquitination and proteasome-mediated degradation, which is accelerated by 24, 25-dihydrolanosterol and the diterpene geranylgeraniol. Statins, competitive inhibitors of HMGCR, deplete cells of mevalonate-derived intermediates and consequently inhibit cell proliferation and induce apoptosis. Clinical application of statins is marred by mixed outcomes on cancer risk, survival and mortality and dose-limiting toxicities, partially resulting from the statin-mediated compensatory upregulation of HMGCR and indiscriminate inhibition of HMGCR in normal and tumor cells. Tumor HMGCR is resistant to the sterol-mediated transcriptional control; consequently HMGCR is upregulated in cancers derived from adrenal gland, blood and lymph, brain, breast, colon, connective tissue, embryo, esophagus, liver, lung, ovary, pancreas, prostate, skin, and stomach. Nevertheless, tumor HMGCR remains sensitive to isoprenoid-mediated degradation. Isoprenoids including monoterpenes (carvacrol, L-carvone, geraniol, perillyl alcohol), sesquiterpenes (cacalol, farnesol, β-ionone), diterpene (geranylgeranyl acetone) and “mixed” isoprenoids (tocotrienols) and derivatives suppress the growth of tumor cells with little impact on non-malignant cells. In cancer cells derived from breast, colon, liver, mesothelium, prostate, pancreas, and skin, statins and isoprenoids including tocotrienols, geraniol, limonene, β-ionone and perillyl alcohol synergistically suppress cell proliferation and associated signaling pathways. A blend of dietary lovastatin and δ-tocotrienol, each at lower-than-effective doses, suppress the growth of implanted murine B16 melanomas in C57BL6 mice. Isoprenoids have potential as adjuvant agents with statins in cancer prevention or therapy to reduce the toxicities of statins.